PENERAPAN METODE EKSPERIMEN PADA MATA KULIAH KONSEP DASAR IPA DALAM MATERI BAGIAN TUBUH TUMBUHAN (Penelitian Kualitatif-Deskriptif pada Mahasiswa PGSD Universitas PGRI Palembang) - Ayurachmawati, Puji (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThis study aims to obtain a description of the implementation of the basic science concept courses with experimental methods and their impact on the activities and learning outcomes of collegesstudents. The research method used is descriptive analysis method. The data were collected on PGSD collegesstudents with 15 peoples. With the experimental method colleges students are given problems by lecturers.Colleges students with their groups conduct discussions, problem analysis, design experiments and report the results of the experiments in front of the class. The average of colleges student activity at meetings 1 and 2 is 72.3% with active category and at meetings 3 and4 is 86.32% with very active category.Colleges student learning outcomes were obtained by using one sample t-test statistic test on N-Gain value. The statistical test results show the difference (mean) is 0.548 with t = 16.968 and the significance level is 0.000 <0.05. It can be concluded that there is a very significant difference between colleges student learning outcomes with the application of experimental methods with before applying the experimental method.Keywords- Experimental method, liveliness, and college student learning outcomes.